Profiling the Dynamics of EMI Effectiveness Factor and Students’ EMI Course Satisfaction: The Case of Vietnam and Taiwan - Tang, Chia-Wei; Le, Nguyen Thi (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This study explored the relationships between English as a medium of instruction (EMI) effectiveness factors and students’ EMI course satisfaction. In addition, responding to the call for adaptive EMI, it also examined how students and teachers’ background characteristics could shape such relationships. Using the convenience sampling method, 821 undergraduate students participated in the survey. The study affirms that three EMI effectiveness factors positively predict student EMI course satisfaction, while characteristics that are related to how students approach learning have the most effect on their satisfaction with EMI courses. These findings also affirm the complexity of student EMI course experiences, when considering both student and teacher demographic and background differences. The moderating effect of English proficiency and prior EMI experience differs significantly among such factors and student satisfaction. This research highlights that a cross-cultural outlook is more influential for Taiwanese students and courses with local teachers, while teaching characteristics are a stronger predictor for male students. The significance of each factor may fluctuate within diverse national contexts and is influenced by students and teacher backgrounds. Understanding and adapting to these contextual nuances will play a key role in elevating overall student satisfaction with EMI courses.